1986
DOI: 10.1145/7921.7923
|View full text |Cite
|
Sign up to set email alerts
|

Interpolants for Runge-Kutta formulas

Abstract: A general procedure for the construction of interpolants for Runge-Kutta (RK) formulas is presented. As illustrations, this approach is used to develop interpolants for three explicit RK formulas, including those employed in the well-known subroutines RKF45 and DVERK. A typical result is that no extra function evaluations are required to obtain an interpolant with O ( h 5 ) local truncation error for the fifth-order RK formula used in RKF45; two extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(106 citation statements)
references
References 9 publications
2
99
0
2
Order By: Relevance
“…For the 6th-order case, a particular strategy is used to obtain a family of schemes. The particular families presented in this paper for the 4th-, 5th-, and 6th-order cases are interesting because they can be viewed as instances of continuous schemes derived from the more traditional interpolation-based approach for the construction of continuous extensions to Runge-Kutta schemes (Enright et al [17]). In each of these cases, the stages which do not satisfy C(p -1), for the /rth-order family, have zero weight polynomials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the 6th-order case, a particular strategy is used to obtain a family of schemes. The particular families presented in this paper for the 4th-, 5th-, and 6th-order cases are interesting because they can be viewed as instances of continuous schemes derived from the more traditional interpolation-based approach for the construction of continuous extensions to Runge-Kutta schemes (Enright et al [17]). In each of these cases, the stages which do not satisfy C(p -1), for the /rth-order family, have zero weight polynomials.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have demonstrated the possibility of generating inexpensive interpolants for explicit Runge-Kutta formulas which are not of the collocation type, in the context of the numerical solution of initial value problems (see, for example, Enright et al [17], Gladwell et al [20], and references therein for some of the earlier work). These interpolants are obtained for Runge-Kutta formula pairs, by constructing extra stages within the current step, thus preserving the one-step nature of the formula.…”
Section: Introductionmentioning
confidence: 99%
“…There are different approaches that can be used to derive SDC CRK formulas. We will use a "bootstrapping" approach similar to that introduced in [6] to derive higher order local interpolants. Other approaches, such as the direct solution of the continuous order conditions, are also possible and could lead to a wider class of suitable SDC CRK formulas.…”
Section: Deriving An Sdc Crkmentioning
confidence: 99%
“…From (6) and (7) we see that as h i → 0 the defect will behave like a linear combination of theq j (τ) over each [x i−1 , x i ]. In the special case that L = 1 the shape of the defect will be the same (as h i → 0) for all problems and all steps.…”
Section: Introductionmentioning
confidence: 99%
“…For many applications it is now recognized that an accurate discrete approximation is not enough and most numerical methods now provide an accurate approximation to the solution of (1) that can be evaluated at any value of x ∈ [a, b]. For a discussion of how this is done and how such methods are used see [10], [3] and [7]. In particular Figures 1 and 2 show the advantage such a method has when it is used to display (or visualize) the solution of an IVP.…”
Section: Introductionmentioning
confidence: 99%